Minimum participation rules in international environmental agreements: Empirical evidence from a survey among delegates in international climate negotiations - Martin Kesternich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Recent contributions to the theoretical and experimental literature suggest that minimum participation rules (MPRs) are able to reduce free-riding incentives and may facilitate cooperation (or at least coordination) at the extensive margin of international environmental agreements. Based on a dataset from a world-wide survey among delegates in international climate negotiations, this paper assesses preferences for different MPRs for a future climate treaty among key players. The empirical findings provide evidence that small countries with low bargaining power rather opt for large minimum membership requirements while industrialized countries push forward the idea of a small carbon club of the largest emitters only. In contrast, delegates from countries in transition try to keep emission thresholds rather low which would allow a future agreement to come into force without their signature.
urn:nbn:de:bsz:180-madoc-387727
Keywords: C72; C92; H41; 330; international climate negotiations; minimum participation rules